The Medieval World: An Illustrated Atlas - Thompson, John M. (USA National Geographic Society, 2009)
Sumptuously illustrating the vivid parade of a thousand years of history, this comprehensive historical atlas concentrates on the Mediterranean world but also shows what happened across the globe between A.D. 400 and 1500 $1 (Bfrom the fall of Rome to the age of discovery. Every page glistens with period works of art, fascinating maps, quotes from medieval figures, close-ups of intriguing artifacts, and rich landscape photographs of the places where battles were fought and monarchs were crowned. For every century, a signature city is spotlighted to represent that era's developments. Time lines connect the many dramatic events that took place in these dark and exciting times, which continue to shape our world today. Written by a team of veteran National Geographic writers, this richly illustrated reference includes full index, reading list, and glossary.s
Includes Colored Illustrations and Index.
Keywords: World Atlas